Comparison of kinetic analysis methods in thermal decomposition of cattle manure by themogravimetric analysis. (November 2017) - Chen, Guanyi; He, Sirong; Cheng, Zhanjun; Guan, Yanan; Yan, Beibei; Ma, Wenchao; Leung, Dennis Y.C.
Highlights: The activation energies keep stable ( α < 60 % ) and then change dramatically. Power law (P3) is an appropriate reaction mechanism for manure decomposition. Vyazovkin method can give the best agreement for cattle manure decomposition. Abstract: The thermogravimetric (TG) experiments of cattle manure were carried out from room temperature to 900 °C at five different heating rates (10, 20, 30, 40 and 50 °C/min) and the kinetics of the main decomposition process were analyzed with different methods. TG curves indicate that the major decomposition process of cattle manure could be roughly divided into three stages. The average activation energy of each stage calculated by Coats-Redfern method are 68.95, 2.63 and 55.32 kJ/mol respectively. The kinetic parameters given by Distributed Activation Energy Model method, Flynn-Wall-Ozawa method and Vyazovkin method are all show that the activation energies keep stable (at around 122.4, 126 and 123.8 kJ/mol respectively) under 60% conversion degree and then changed dramatically (ranging from 129.9 to 454.9 kJ/mol). Power law (P3) was determined as an appropriate reaction mechanism using master-plots method. The kinetic parameters calculated by Vyazovkin method can give the best agreement with the experimental results.